Key to species of the genus Riseveinus Li & Wang, 1995 (Hemiptera: Cicadellidae: Evacanthinae) with description of a new species - Gou, Guangli; Xing, Jichun (Zootaxa, 2024)
A new evacanthine leafhopper species Riseveinus elongatus sp. nov., is described and illustrated from Yunnan Province, China. A key is given to distinguish all species of the genus. The type specimen of the new species is deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).